Developing secure android application with encrypted database file using sqlcipher - Rachmawan, Ardiansa (2014)
The number of smartphone users is increasing every year. The technology changes the large form of personal computer become portable computer called smartphone. Todays the most popular operating system for smartphones is android, it is recorded that more than 1 billion android devices was activated. With this large number of today’s android users, the possibility risk of this device lost or stolen is also high. The problem comes when the users have confidential data or information in database of android application. This secret information inside the phone shouldn’t be accessed by other people except the authorized users. The information security lead to protecting information from unauthorized access, use, disclosure, disruption, modification, perusal, inspection, recording or destruction. To react the problem stated, we propose to develop secure android application with encrypted database file using SQLCipher.